Learning malware analysis : explore the concepts, tools, and techniques to analyze and investigate Windows Malware - Monnappa, K. A. (Birmingham, UK : Packt Publishing, Limited, 2018)
Malware analysis and memory forensics are powerful analysis and investigation techniques used in reverse engineering, digital forensics, and incident response. With adversaries becoming sophisticated and carrying out advanced malware attacks on critical infrastructures, data centers, and private and public organizations, detecting, responding to, and investigating such intrusions is critical to information security professionals. Malware analysis and memory forensics have become must-have skills to fight advanced malware, targeted attacks, and security breaches. This book teaches you the concepts, techniques, and tools to understand the behavior and characteristics of malware through malware analysis. It also teaches you techniques to investigate and hunt malware using memory forensics. This book introduces you to the basics of malware analysis, and then gradually progresses into the more advanced concepts of code analysis and memory forensics. It uses real-world malware samples, infected memory images, and visual diagrams to help you gain a better understanding of the subject and to equip you with the skills required to analyze, investigate, and respond to malware-related incidents.
Introduction to Malware Analysis -- Static Analysis -- Dynamic Analysis -- Assembly Language and Disassembly Primer -- Disassembly Using IDA-- Debugging Malicious Binaries -- Malware Functionalities and Persistence -- Code Injection and Hooking -- Malware Obfuscation Techniques -- Hunting Malware Using Memory Forensics -- Detecting Advanced Malware Using Memory Forensics.
Includes index.
Keywords: MICROSOFT WINDOWS (COMPUTER FILE)